Pornografi dalam Perspektif Hukum Islam dan Hukum Positif - Ariyanti, Vivi (Al-Manahij: Jurnal Kajian Hukum Islam, 2010)
Pornography which has impacts in human's life is already controlled by al-Qur’an and Pornography Act (UU No. 44/2008).